Service Improvement Priorities of Train Transport Service: Evidence from Indonesian Economy-Premium Train - Tina Agustien; Tulus Haryono (Jurnal Internasional Penelitian Bisnis Terapan, 2021)
The Indonesian Railway Company (PT KAI) may have sustainable growth due to passengers' quality services. This study determines influential indicators and service improvement priorities for the economy-premium train in Indonesia using 284 respondents. An online questionnaire was used to collect data, while the sample was determined using judgment sampling methods. The study used the Exploratory Factor Analysis (EFA) and the Importance-Performance Analysis (IPA). The results show that passengers felt satisfied with the completeness of emergency equipment, security and safety, and professional train staff. However, they were not satisfied with TV show contents, food and beverage prices, and legroom on chairs. The EFA results show nine dimensions and 41 influential indicators of the economy-premium train service qualities. According to the IPA results, the service priorities that should be improved by PT KAI include the availability of internet access and the cabin facilities, especially TV show contents and legroom on chairs. These results can help PT KAI to increase its Customer Satisfaction Index (CSI) score to meet the respondents' expectations and increase the satisfaction and loyalty of the economy-premium train passengers.